Using limit concepts, the matching pairs are:
A - 3
B - 1
C - 2
D - 4
The end behavior of a function f(x) is given by it's limit as x goes to infinity.
Function A:
[tex]f(x) = -2x + 3[/tex], then:
[tex]\lim_{x \rightarrow -\infty} f(x) = \lim_{x \rightarrow -\infty} -2x = -2(-\infty) = \infty[/tex]
[tex]\lim_{x \rightarrow \infty} f(x) \lim_{x \rightarrow -\infty} -2x = -2(\infty) = -\infty[/tex]
Thus, inverse directions, so matching pair with 3.
Function B:
[tex]f(x) = x^2 - 6x + 3[/tex], then:
[tex]\lim_{x \rightarrow -\infty} f(x) = \lim_{x \rightarrow -\infty} x^2 = (-\infty)^2 = \infty[/tex]
[tex]\lim_{x \rightarrow \infty} f(x) \lim_{x \rightarrow -\infty} x^2 = (\infty)^2 = \infty[/tex]
Always positive, so matching pair with 1.
Function C:
[tex]f(x) = 1 - x^2 + 2x^3[/tex], then:
[tex]\lim_{x \rightarrow -\infty} f(x) = \lim_{x \rightarrow -\infty} 2x^3 = 2(-\infty)^3 = -\infty[/tex]
[tex]\lim_{x \rightarrow \infty} f(x) \lim_{x \rightarrow -\infty} 2x^3 = 2(\infty)^3 = \infty[/tex]
Same directions, thus, matching pair with 2.
Function D:
[tex]f(x) = 7 - x^4[/tex], then:
[tex]\lim_{x \rightarrow -\infty} f(x) = \lim_{x \rightarrow -\infty} -x^4 = -(-\infty)^4 = -\infty[/tex]
[tex]\lim_{x \rightarrow \infty} f(x) \lim_{x \rightarrow -\infty} -x^4 = -(\infty)^4 = -\infty[/tex]
Always negative, so matching pair with 4.
A similar problem is given at https://brainly.com/question/9368215